Constrained Two-Dimensional Inversion of Gravity Data - Grandis, Hendra; Dahrin, Darharta (Journal of Mathematical and Fundamental Sciences, 2014)
The non-uniqueness in the solution of gravity inversion poses a major problem in the interpretation of gravity data. To overcome this ambiguity, "a priori" information is introduced by minimizing a functional that describes the geometrical or physical properties of the solution. This paper presents a 2D gravity inversion technique incorporating axes of anomalous mass concentration as constraints. The inverse problem is formulated as a minimization of the moment of inertia of the causative body with respect to the axes of the mass concentration. The proposed method is particularly applicable to homogeneous, linear mass distributions, such as mineralization along faults and intruded sills or dikes. Inversions of synthetic and field data illustrate the versatility of the implemented algorithm.